A Study of Catholicism: An Interdisciplinary Faculty Seminar - Heft, James (Horizons, 2002)
This essay describes an intensive eight-month long interdisciplinary faculty seminar which brought together faculty from the social sciences and humanities to explore, with different methodologies, the nature and traditions of Catholicism. It describes the way in which the seminar was organized, the participants selected, the syllabus chosen and how the discussion unfolded. It concludes with an evaluation by the author of what was learned, and then provides a brief description of the research projects undertaken by the seminar participants.